Competition among governments: The state's two roles in a globalized world - Viktor J. Vanberg (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik, 2010)
It is common wisdom that the process of globalization has intensified competition among governments. The precise nature of such competition is, however, less well understood. The purpose of this paper is to explore how the competitive pressure that globalization exerts on governments affects the legal-institutional foundations of markets and states. Its main thesis is that globalization demands a stricter distinction between two different functions of the state, functions that have traditionally not been clearly separated. The first is the role of the state as the joint enterprise of its citizens, i.e. as the agency through which citizens provide for themselves the public services they want. The second is its role as a 'territorial enterprise,' i.e. as the agency that defines and enforces the rules of the 'national market,' i.e. the legal-institutional terms under which agents, citizens as well as non-citizens, may do business within its jurisdiction. Making this distinction has important implications for taxation and regulation because individuals' choices concerning their citizenship are determined by other considerations than their choices as 'market-users' or 'jurisdiction-users.' Accordingly, governments face different constraints in defining the terms of citizenship on the one hand and in defining the terms for 'jurisdiction-users' on the other.
Keywords: 330